Metabolic adaptations to targeted therapy in FLT3 mutated acute myeloid leukaemia. (23rd February 2017) - Gallipoli, Paolo; Costa, Ana S H; Vohra, Shabana; Castro, Cecilia; Griffin, Jules; Frezza, Christian; Huntly, Brian
Abstract: Background: Acute myeloid leukaemia has a dismal outlook. FLT3 tyrosine kinase (TK) activating mutations ( FLT3 mut) are present in 30% of cases and are predictive of a worse outcome. Although metabolic reprogramming has been recognised as a hallmark of cancer cells, little is known about its role in acute myeloid leukaemia. Published gene expression datasets show that glycolytic, citric acid cycle, and oxidative phosphorylation genes are upregulated in FLT3 mut patient samples at diagnosis. We aimed to study metabolic changes in FLT3 mut disease upon targeted inhibition of its TK activity in an attempt to unveil novel therapeutic vulnerabilities. Methods: Liquid chromatography coupled to mass spectrometry, using stable isotope-based carbon flux tracing, and an extracellular flux analyser (Seahorse, Agilent Technologies, Santa Clara, CA, USA) were used to assess metabolic changes in FLT3 mut human and murine cells after FLT3 TK inhibition by the specific inhibitor AC220. Gene expression changes were measured in the same conditions by RNA sequencing. Fluorescence-activated cell sorting was used to measure changes in viability and reactive oxygen species after inhibition of TK activity in various culture conditions. Findings: We confirmed in both human and murine cells that FLT3 mut cells displayed an increased glycolytic (maximal glycolytic capacity, extracellular acidification rate of 80·64 mpH/min in FLT3 mut vs 59·09 in FLT3 wildtype, p<0·001) and respiratory capacity (maximal respiratory capacity, oxygen consumption rate of 326·4 pmoles/min in FLT3 mut vs 180·9 in FLT3 wildtype, p<0·001). Upon treatment with AC220, these metabolic phenotypes were reversed. However, whereas glucose uptake was significantly reduced upon TK inhibition (p<0·001), glutamine uptake was not affected. Metabolic flux analysis with [U − 13 C]glutamine suggested that glutamine was diverted to glutathione production upon AC220 treatment. FLT3 mut cells displayed a large increase in concentration of reactive oxygen species upon AC220 treatment when grown in the absence of glutamine (fold increase of reactive oxygen species normalised to untreated cells 4·59 without glutamine vs 2·74 with glutamine, p<0·001), and these changes correlated with a significant reduction in viability (relative viability normalised to untreated 34·6% without glutamine vs 62·5% with glutamine, p<0·001) in the same conditions. Interpretation: Our data suggest that FLT3 mut acute myeloid leukaemia cells have increased respiratory and glycolytic capacity that is reversed by TK inhibition. Upon AC220 treatment glutamine metabolism becomes a metabolic dependency of FLT3 mut disease, as glutamine is channelled towards glutathione production and reactive oxygen species detoxification, and protects them from cell death. This process could be exploited therapeutically by a combination of glutaminolysis or glutathione biosynthesis inhibitors with FLT3 TK inhibitors. Funding: Wellcome Trust.